Pengaruh PSBB Volume Perdagangan Terhadap Stock Return pada Perusahaan Layanan Perdagangan dan Investasi Sub Sektor Pariwisata Restoran dan Hotel - Maria Marsilinda Paku; Risal Rinofah; Ratih Kusumawardhani (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the effect of Large-Scale Social Restrictions (PSBB) and trading volume on stock returns of trade and investment service companies in the tourism, restaurant, and hotel sub-sectors. These sub-sectors were selected due to their significant exposure to the impacts of the COVID-19 pandemic, particularly restrictions on public mobility and face-to-face interactions, which drastically affected business operations and revenue streams. The research applies a quantitative method with an associative approach. Secondary data were obtained from the Indonesia Stock Exchange (IDX) and official government publications concerning the PSBB policy during the pandemic period. The population of this study includes all tourism, restaurant, and hotel companies listed on the IDX during the years 2020–2021. A purposive sampling technique was used to determine the sample. The data were analyzed using multiple linear regression analysis with the help of SPSS software to test the simultaneous and partial influence of the independent variables on the dependent variable. The results indicate that the PSBB policy has a significant negative effect on stock returns. This finding aligns with the expectation that movement restrictions and reduced consumer activity would negatively affect business performance and investor sentiment. In contrast, trading volume has a significant positive effect on stock returns, suggesting that increased trading activity may reflect higher investor confidence and speculation, which contributes to price appreciation. These findings offer valuable theoretical insights into the behavior of capital markets during a crisis, particularly in sectors highly sensitive to government policies and public health emergencies. Practically, the study provides useful information for companies, investors, and policymakers in developing risk mitigation strategies, enhancing investment decision-making, and formulating adaptive responses to future crises with similar characteristics.